Sleep disorders in patients with COVID-19 - Marina A. Samushiya; Natalia V. Mironova; Mikhail G. Poluektov (ZAO "Consilium Medicum", 2021)
Sleep disorders often accompany COVID-19 and are a part of post-COVID syndrome. Some of the sleep disorders that occur in patients hospitalized for COVID-19 can be attributed to acute forms of insomnia. This type of sleep disorders is due to special conditions associated with hospitalization, and is short-term. Other sleep disorders appear as a part of anxiety-depressive symptoms diagnosed in patients with COVID-19. These symptoms can be classified as nosogenies psychogenic disorders that are associated with diagnosis of coronavirus infection; somatogenies psychopathological conditions resulting from pathological effects on the central nervous system of somatic and neurological complications of COVID-19; iatrogenies mental disorders that occur due to the intake of medication. Currently, information on the impact of sleep quality on the severity of COVID-19 and the effectiveness of treatment for post-COVID syndrome is accumulating. This review provides up-to-date information on sleep disorders in patients with COVID-19 and the principles of their therapy.